Overview of Social Support in Orphanages at Alma Oebufu Sisters, Kupang City - Dwira Putri Talita Alvoni Mite (Journal of Mandalika Social Science, 2026)
Humans as social beings cannot live alone without interaction with others. Social support is one of the important factors in shaping psychological well-being, especially for individuals who are in vulnerable conditions such as children in orphanages. Orphanages function as family substitutes that provide nurturing, education, and moral and spiritual guidance. In principle, children have the right to be cared for by caregivers who are most responsible for the growth and development of children. This study seeks to describe the form of social support received by children at the Alma Sisters Orphanage, Kupang City, as well as how this support affects their daily lives